ANALYZING COLLAGE AS A COMMUNICATION ACT IN THE DIGITAL AGE BASED ON THE DADAISM RENEWAL MOVEMENT'S SPIRIT - Dewi, Agustina Kusuma; Dwinaya, Levita (Sanata Dharma University, 2024)
Collage combines the semiotic tradition of Roland Barthes, the phenomenological tradition of Edmund Husserl, the critical tradition of Karl Marx, and the point of view of Jurgen Habermas in visual communication. The collage technique creates trans-aesthetic elements and double codes, a Dadaist method of encoding signs. Building on previous research, this study explores collage art as a communication act and its process in the digital era. Digital photography technology and computer software facilitate quicker and easier creation of collage art, emphasizing the fundamental concept of